Circulating cell‐free DNA for target quantification in hematologic malignancies: Validation of a protocol to overcome pre‐analytical biases. Issue 1 (19th October 2022) - Soscia, Roberta; Della Starza, Irene; De Novi, Lucia Anna; Ilari, Caterina; Ansuinelli, Michela; Cavalli, Marzia; Bellomarino, Vittorio; Cafforio, Luciana; Di Trani, Mariangela; Cazzaniga, Giovanni; Fazio, Grazia; Santoro, Alessandra; et al.
Abstract: Circulating tumor DNA (ctDNA) has become the most investigated analyte in blood. It is shed from the tumor into the circulation and represents a subset of the total cell‐free DNA (cfDNA) pool released into the peripheral blood. In order to define if ctDNA could represent a useful tool to monitor hematologic malignancies, we analyzed 81 plasma samples from patients affected by different diseases. The results showed that: (i) the comparison between two different extraction methods Qiagen (Hilden, Germany) and Promega (Madison, WI) showed no significant differences in cfDNA yield, though the first recovered higher amounts of larger DNA fragments; (ii) cfDNA concentrations showed a notable inter‐patient variability and differed among diseases: acute lymphoblastic leukemia and chronic myeloid leukemia released higher amounts of cfDNA than chronic lymphocytic leukemia, and diffuse large B‐cell lymphoma released higher cfDNA quantities than localized and advanced follicular lymphoma; (iii) focusing on the tumor fraction of cfDNA, the quantity of ctDNA released was insufficient for an adequate target quantification for minimal residual disease monitoring; (iv) an amplification system proved to be free of analytical biases and efficient in increasing ctDNA amounts at diagnosis and in follow‐up samples as shown by droplet digital PCR target quantification. The protocol has been validated by quality control rounds involving external laboratories. To conclusively document the feasibility of a ctDNA‐based monitoring of patients with hematologic malignancies, more post‐treatment samples need to be evaluated. This will open new possibilities for ctDNA use in the clinical practice.